Analysis of a DOAS operation in different Spanish climates using an experimentally validated TRNSYS model. Issue 2 (2nd April 2020) - Martínez, Pedro J.; Martínez, Pedro; Soto, Victor M.; Rodriguez, Juan; Bujedo, Luis A.
Abstract: Current ventilation airflow rates imposed by building regulations eventually force HVAC systems to remove high latent loads. Dedicated outdoor air systems (DOASs) equipped with a desiccant wheel, are an alternative to conventional refrigeration equipment for humidity control in buildings. This paper studies the operation of a DOAS intended to remove the ventilation air and space latent load in different Spanish climates during the summer season. The model developed in TRNSYS was validated with experimental data using the root mean standard error (RMSE). Maximum RMSE of 0.94 °C and 0.472 g/kg were obtained for the temperatures and humidity ratios of the process and regeneration airflows. The RMSE for the compressor power input was of 52.2 W. The results obtained with the developed model showed that the DOAS exhibited better performance in humid climates with moderate temperatures (Bilbao and Barcelona). It was also found that its application in dry climates (Madrid) was not appropriate, and that a high outdoor temperature lowered the DOAS efficiency when comparing cities with similar latent loads (Bilbao and Sevilla) or when comparing residential and commercial schedules.